CT chest with pulmonary angiography as a diagnostic tool in clinically suspected RT-PCR-negative COVID-19 pneumonia with pulmonary artery aneurysm - Aniket Agarwal,; Niraj Kumar, (Indian Journal of Case Reports, 2021)
COVID-19 caused by the SARS-CoV-2 strain of coronavirus was officially recognized as a pandemic by the World Health Organization on March 11, 2020. Most patients present with mild disease. However, elderly patients and those with coexisting comorbid conditions such as diabetes and hypertension are more likely to develop severe disease. Definitive diagnosis is by RT-PCR test and CT scan is an adjunct modality. By virtue of being a hypercoagulable state with cytokine storm and microthrombosis as key components in pathogenesis, additional finding of pulmonary thrombosis in such patients should increase diagnostic accuracy. We report an interesting case with clinical and radiological features supporting COVID-19 pneumonia such as patchy ground-glass opacities with consolidation in bilateral peripheral lung fields along with segmental pulmonary thrombosis. The conundrum in the case arises from the negative RT-PCR test and presence of pulmonary artery aneurysm which could be an incidental finding or sequelae of COVID-19, which remains to be studied.